Nilai-Nilai Pendidikan Agama Hindu Dalam Cerita Batur Taskara - I Wayan Sudiarta (Cetta: Jurnal Ilmu Pendidikan, 2018)
The story of Batur Taskara is one of the literary works which is an ancestral heritage that is rich in the values of Hindu religious education, where it deserves attention in the preservation and development of the nation's culture. Efforts made to preserve and develop it, in this article are devoted to examining one old literary work, namely Batur Taskara Story. The story of Batur Taskara tells about the behavior of a criminal later regretting his actions and then decides to repent and eventually dies from being killed. In this study discuss two things, namely (1) what is the synopsis of the Story of Batur Taskara? and (2) What are the values of Hindu Religion Education in the Story of Batur Taskara? This research uses literature research method. The type of data is the primary data, namely the original manuscript from the Batur Task Story and secondary data, namely literature studies or relevant documents. Collecting data used with document recording methods. Data analysis uses descriptive analysis with induction and argumentation techniques. The results of this study obtained results (1) Synopsis Stories Batur Taskara namely Batur Taskara is a criminal who later regretted the last act of dying of being killed, The values of Hindu Religion contained include: Tat Twam Asi, Panca Yama Bratha, Panca Niyama Bratha and Dasa Yama Bratha.